2001
DOI: 10.1073/pnas.041483198
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor alpha , not beta , is a critical link in estradiol-mediated protection against brain injury

Abstract: Estradiol protects against brain injury, neurodegeneration, and cognitive decline. Our previous work demonstrates that physiological levels of estradiol protect against stroke injury and that this protection may be mediated through receptor-dependent alterations of gene expression. In this report, we tested the hypothesis that estrogen receptors play a pivotal role in mediating neuroprotective actions of estradiol and dissected the potential biological roles of each estrogen receptor (ER) subtype, ER␣ and ER␤,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
276
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(295 citation statements)
references
References 53 publications
16
276
1
2
Order By: Relevance
“…Previous studies have shown no physiological differences between groups (Dubal et al, 2001;McCullough et al, , 2005. At either 14 or 42 days of reperfusion, the brain was harvested for histological examination.…”
Section: Focal Cerebral Ischemia Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have shown no physiological differences between groups (Dubal et al, 2001;McCullough et al, , 2005. At either 14 or 42 days of reperfusion, the brain was harvested for histological examination.…”
Section: Focal Cerebral Ischemia Modelmentioning
confidence: 97%
“…Female ERKO and BERKO mice, back crossed onto a C57BL/6J genetic background (Dubal et al, 2001;reviewed in Hewitt et al (2005)) and aromatase-deficient (ArKO on SV129) mice were compared directly to their respective gonadally intact agematched female WT littermates.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…One view is that both nuclear and plasma membrane-associated ERs might be products of the same genes (Razandi et al, 1999, Boulware et al, 2005, Pedram et al, 2006, Szegõ et al, 2006, Dewing et al, 2007. This belief stems primarily from the fact that many of the rapid effects of E2 can be induced by selective ERα or ERβ ligands, antagonized by the ER antagonist, ICI 182,780, or are lost in animals bearing mutations in ERα and/or ERβ genes (Couse and Korach, 1999, Singer et al, 1999, Dubal et al, 2001, Wade et al, 2001, Abraham et al, 2003, Boulware et al, 2005. Another view is that estrogen activates a unique membrane ER (mER) (Gu et al, 1999, Toran-Allerand, 2004, Toran-Allerand, 2005, Qiu et al, 2006b).…”
Section: Membrane-initiated Signaling Of E2mentioning
confidence: 99%
“…This belief stems primarily from the fact that many of the rapid effects of E 2 can be induced by selective ERα or ERβ ligands, antagonized by the ER antagonist, ICI 182,780 or are lost in animals bearing mutations in ERα and/or ERβ genes [15,46,[49][50][51][52]. In ERα-deficient mice, rapid estrogen responses in certain regions of the mouse brain are lost [53], whereas the rapid action of estradiol in mouse hippocampal and arcuate neurons is not [18,54].…”
Section: Mer Is Distinct From Erα and Erβmentioning
confidence: 99%